Novel roles of non-coding brain RNAs in health and disease - Hermona Soreq (Frontiers Research Topics, 2014)
Non-coding RNAs (ncRNAs), and in particular microRNAs are rapidly becoming the focus of research interest in numerous basic and translational fields, including brain research; and their importance for many aspects in brain functioning merits special discussion. The wide-scope, multi-targeted and highly efficient manner of ncRNA regulatory activities draws attention to this topic by many, but the available research and analysis tools and experimental protocols are still at their infancy, and calls for special discussion given their importance for many aspects in brain functioning. This eBook is correspondingly focused on the search for, identification and exploration of those non-coding RNAs whose activities modulate the multi-leveled functions of the eukaryotic brain. The different articles strive to cover novel approaches for identifying and establishing ncRNA-target relationships, provide state of the art reports of the affected neurotransmission pathways, describe inherited and acquired changes in ncRNA functioning and cover the use of ncRNA mimics and blockade tools for interference with their functions in health and disease of the brain. Non-coding RNAs are here to stay, and this exciting eBook provides a glimpse into their impact on our brain's functioning at the physiology, cell biology, behavior and immune levels.